2015
DOI: 10.1159/000441217
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Responses to Tyrosinase-Derived Self-Peptides in Patients with Leukoderma Induced by Rhododendrol: Implications for Immunotherapy Targeting Melanoma

Abstract: Background: Rhododendrol, a phenolic compound contained in lightening/whitening cosmetics, can bind and inhibit tyrosinase and was reported to induce leukoderma in Japan. Only 2% of the cosmetics users are affected, and tacrolimus is effective in treatment of the condition. Objective: To test the hypothesis that the disease is an autoimmune disorder. Methods: Short-term T-cell lines were established using peripheral blood mononuclear cells from 8 patients with human melanoma-associated and tyrosinase-derived s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Activation of the immune system against melanocytes is proposed to be a cause of RD-induced leukoderma, because the immunosuppressant FK506 can partially restore melanin synthesis in human patients (Suzuki et al, 2014;Takagi et al, 2016), despite the lack of effect of FK506 on our zebrafish model (data not shown). The transplantation of mouse melanoma B16F10 cells that had been pretreated with RD produces hypopigmented hairs in host mice, suggesting the involvement of acquired immune responses against melanocytes (Takagi et al, 2016).…”
Section: Discussionmentioning
confidence: 81%
“…Activation of the immune system against melanocytes is proposed to be a cause of RD-induced leukoderma, because the immunosuppressant FK506 can partially restore melanin synthesis in human patients (Suzuki et al, 2014;Takagi et al, 2016), despite the lack of effect of FK506 on our zebrafish model (data not shown). The transplantation of mouse melanoma B16F10 cells that had been pretreated with RD produces hypopigmented hairs in host mice, suggesting the involvement of acquired immune responses against melanocytes (Takagi et al, 2016).…”
Section: Discussionmentioning
confidence: 81%
“…In severe cases, auto‐immune reaction might be a key factor. Takagi et al reported that antibodies to tyrosinase were involved in RIL based on a study using peripheral blood of the patients. Thus, there is a possibility that auto‐immune reaction targeting degenerative melanosomes may lead to subsequent changes in certain conditions and/or patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosinase peptide‐specific cytotoxic T cells have been suggested to be involved in a melanocyte‐specific cytotoxic mechanism. 26 When T‐cell lines were established from peripheral blood monocytes derived from eight patients with RDL (seven of whom were HLA‐DR4 + ), a tyrosinase peptide‐specific T‐cell response, restricted to major histocompatibility complex (MHC) classes I and II, was observed. It is assumed that the antigenicity of tyrosinase peptide is altered to a non‐natural form upon binding to RD (a concealed antigen), and MHC‐restricted cytotoxic T cells may specifically attack melanocytes in the presence of RD.…”
Section: Mechanism Of Rdl Developmentmentioning
confidence: 99%
“…It is assumed that the antigenicity of tyrosinase peptide is altered to a non‐natural form upon binding to RD (a concealed antigen), and MHC‐restricted cytotoxic T cells may specifically attack melanocytes in the presence of RD. 26 However, there remain certain unresolved issues, particularly with respect to the limited number of cases, and it is unknown whether the concealed tyrosinase antigen is actually presented on melanocytes. In addition, the relationship between leukoderma symptoms and tyrosinase reactivity remains poorly understood.…”
Section: Mechanism Of Rdl Developmentmentioning
confidence: 99%
See 1 more Smart Citation